2001
DOI: 10.1002/1521-3765(20010119)7:2<490::aid-chem490>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

The Facile Preparation of Weakly Coordinating Anions: Structure and Characterisation of Silverpolyfluoroalkoxyaluminates AgAl(ORF)4, Calculation of the Alkoxide Ion Affinity

Abstract: Purified LiAlH4 reacts with fluorinated alcohols HORF to give LiAl(ORF)4 (RF=-CH(CF3)2, 2a; -C(CH3)(CF3)2, 2b; -C(CF3)3, 2c) in 77 to 90% yield. The crude lithium aluminates LiAl(ORF)4 react metathetically with AgF to give the silver aluminates AgAl(ORF)4 (RF=-CH(CF3)2, 3a; -C(CH3)(CF3)2, 3b; -C(CF3)3, 3c) in almost quantitative yield. The solid-state structures of solvated 3a-c showed that the silver cation is only weakly coordinated (CN(Ag)=6-10; CN = coordination number) by the solvent and/or weak cation - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
448
0
28

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 490 publications
(490 citation statements)
references
References 66 publications
14
448
0
28
Order By: Relevance
“…4 ] -was applied as the simple to use oxidizing agent of choice (eq. 2), which was synthesized according to the procedure established in our group [33].…”
Section: -(Bohfip 2 )Fc 1 and 11'-(bohfip 2 ) 2 Fcmentioning
confidence: 99%
See 2 more Smart Citations
“…4 ] -was applied as the simple to use oxidizing agent of choice (eq. 2), which was synthesized according to the procedure established in our group [33].…”
Section: -(Bohfip 2 )Fc 1 and 11'-(bohfip 2 ) 2 Fcmentioning
confidence: 99%
“…To combine a decent stability with sufficient Lewis acidity, we chose the fluorinated alkoxide 1,1,1,3,3,3-hexafluoro-2-propoxy ligand (Ohfip) for the boryl residue. The Ohfip-ligand was proven to provide suitable Lewis acidity to an electron-deficient central atom, e.g., in the related B(Ohfip) 3 , as well as in monomeric Al[OC(CF 3 ) 3 ] 3 or dimeric Al 2 (Ohfip) 6 [30][31][32][33][34]. Carpenter and coworkers suggested that oxidation enhances the Lewis acidity of ferrocenylboranes, so that the B center in certain borylferrocinium compounds abstracts a fluoride from a [BF 4 ] -counteranion [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 and Krossing's "Teflon ball" PFTB. 22 There are only few examples of halogen-free lipophilic anions with low nucleophilicity. One class of these halogen-free anions are carboranates such as the [CB 11 H 12 ] -anion ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available IPrMCl (M = Cu, Au; IPr = 1,3-bis(diisopropylphenyl)imidazol-2-ylidene) in combination with Li + [Al(pftb) 4 ] À (pftb = perfluoro-tert-butoxy) 11,12 as chloride scavenger were found to be suitable starting materials allowing the isolation of readily available LA-P 4 adducts. The complexation of P 4 was achieved by dropwise addition of a solution of IPrMCl (1 equiv.…”
mentioning
confidence: 99%